1984
DOI: 10.1002/ana.410150112
|View full text |Cite
|
Sign up to set email alerts
|

Selective memory improvement and impairment in temporal lobectomy for epilepsy

Abstract: Reexamination of 23 patients 1 year after elective anterior temporal lobectomy for intractable complex partial (psychomotor) seizures showed a reduction in certain memory functions combined with an improvement in others. Both improvement and impairment in selective memory functions were related to the degree of postoperative seizure reduction as well as to the side of the remaining temporal lobe. The results imply that uncontrolled seizures interfered with the memory functions of the temporal lobe contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
79
3
5

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(104 citation statements)
references
References 14 publications
17
79
3
5
Order By: Relevance
“…undergoing left ATL exhibited improvement in recall of visual designs, while those undergoing right ATL demonstrated improvement in paragraph recall (3). Similar findings were seen in other centers.…”
Section: What Happens To the Brain Following Anterior Temporal Lobe Rsupporting
confidence: 86%
“…undergoing left ATL exhibited improvement in recall of visual designs, while those undergoing right ATL demonstrated improvement in paragraph recall (3). Similar findings were seen in other centers.…”
Section: What Happens To the Brain Following Anterior Temporal Lobe Rsupporting
confidence: 86%
“…Previous reports using unstandardized memory outcome techniques have found that left ATL groups display statistically significant declines on measures of verbal memory and visual confrontation naming after dominant temporal lobe resection (28,30,3 1). Significant visual memory decline also has been reported after right ATL, although not as consistently (32)(33)(34)(35). These within-group findings suggest that these statistically significant results may not be clinically significant after controlling for normal test-retest variability.…”
Section: Discussionmentioning
confidence: 90%
“…It was frequently reported that left temporal lobectomy provokes verbal memory deficit, and right temporal lobectomy, visual memory deficit (50)(51)(52)(53)(54)(55). However, there are some discrepancies in the literature concerning the neuropsychological significance of quantitative MR results (23, [56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%